The polarization mode of the auroral radio emission from the early-type star HD 142301. (24th September 2018) - Leto, P; Trigilio, C; Oskinova, L M; Ignace, R; Buemi, C S; Umana, G; Cavallaro, F; Ingallinera, A; Bufano, F; Phillips, N M; Agliozzo, C; Cerrigone, L; et al.
ABSTRACT: We report the detection of the auroral radio emission from the early-type magnetic star HD 142301. New VLA observations of HD 142301 detected highly polarized amplified emission occurring at fixed stellar orientations. The coherent emission mechanism responsible for the stellar auroral radio emission amplifies the radiation within a narrow beam, making the star where this phenomenon occurs similar to a radio lighthouse. The elementary emission process responsible for the auroral radiation mainly amplifies one of the two magneto-ionic modes of the electromagnetic wave. This explains why the auroral pulses are highly circularly polarized. The auroral radio emission of HD 142301 is characterized by a reversal of the sense of polarization as the star rotates. The effective magnetic field curve of HD 142301 is also available making it possible to correlate the transition from the left to the right-hand circular polarization sense (and vice versa) of the auroral pulses with the known orientation of the stellar magnetic field. The results presented in this letter have implications for the estimation of the dominant magneto-ionic mode amplified within the HD 142301 magnetosphere.